Re-establishment of Devibursaphelenchus Kakuliya, 1967 (Nematoda, Aphelenchoididae) and proposal for a new combination of several Bursaphelenchus species (Journal of Nematode Morphology and Systematics, 2012)
Among theca 100 known species of Bursaphelenchus, there are a few questionable taxa which share some morphological characters with this genus and other characters with the genera of the subfamily Ektaphelenchinae. B. lini and B. eproctatus are characterized, amongst other features, by having bursa, wide-lumened stylet, well developed oblong median bulb with posterior valve plates, and obscure/non-functional rectum and anus, that is, the same combination of diagnostic characters as B. typographi (syn. Devibursaphelenchus typographi). In this context, Devibursaphelenchus Kakuliya, 1967, for a long time regarded as a junior synonym of Bursaphelenchus, is re-established as a genus belonging to Ektaphelenchinae, and its generic definition is expanded. It is characterized by its lip region offset; V > 75; male tail conoid and curved ventrad, with terminal bursa, as in Bursaphelenchus; strong spicules with high condylus and, sometimes, hook-like distal terminus; absence of vulval flap; obscure rectum and anus in females, strongly sclerotized vagina, posterior placement of valve plates in metacorpus, lip region slightly trapezoid, and widelumened stylet ca 20 μm long in common with Ektaphelenchus. Devibursaphelenchus lini (Braasch, 2004) comb. n. is proposed for Bursaphelenchus lini, D. eproctatus (Sriwati, Kanzaki, Phan & Futai, 2008) comb. n. for B. eproctatus, D. teratospicularis (Kakuliya & Devdariani, 1965) recomb. n. for B. teratospicularis and D. hunanensis (Yin, Fang & Tarjan, 1988) comb. n. for B. hunanensis. The taxonomic position of B. abruptus Giblin-Davis, Mundo-Ocampo, Baldwin, Norden & Batra, 1993 and B. minutus Walia, Negi, Bajaj & Kalia, 2003 is discussed.